SLUM REVITALIZING PLAN OF BAGHDADIYAH BY SPATIAL RE-MODELING CONFIGURATION - Herika Muhamad Taki (Department of Urban and Regional Planning, Diponegoro University, 2017)
Baghdadiyah is a neighborhood of Jeddah Downtown, Kingdom of Saudi Arabia. Inhabitants of this area come from multi-ethnic and mostly low-income residents. The high density of the area affects land use more concisable. Consequently, the beauty of the city which was used to be historic sites of Jeddah is down-grading. This study proposed to revitalize city plan for a better quality of life. The aim of this study was to re-shape a slum area and to improve the spatial configuration of urban structure based on the recent condition. The method involved several approaches: recognizing a theoretical basic concept of the slum, applying spatial re-configuration, analyzing the existing conditions and re-constructing new syntactical properties. The result of this study shared a new design of slum revitalizing plan for Baghdadiyah configuring dominated patterns of integration and connection. Adequate transport networks would reshape the city building profile.